x+1x=13−−√,x+1x=13,x + \frac{1}{x} = \sqrt {13} {\text{,}} then 3x(x2−1)" role="presentation">3x(x2−1)3x(x2−1)\frac{{3x}}{{\left( {{x^2} - 1} \right)}} equal to?" /> x+1x=13−−√,x+1x=13,x + \frac{1}{x} = \sqrt {13} {\text{,}} then 3x(x2−1)" role="presentation">3x(x2−1)3x(x2−1)\frac{{3x}}{{\left( {{x^2} - 1} \right)}} equal to?" /> x+1x=13−−√,x+1x=13,x + \frac{1}{x} = \sqrt {13} {\text{,}} then 3x(x2−1)" role="presentation">3x(x2−1)3x(x2−1)\frac{{3x}}{{\left( {{x^2} - 1} \right)}} equal to?" />
Post your Comments